Scottish Female Voices - Vondráková, Jana (Univerzita Pardubice, 2022)
This bachelor thesis aims to analyze position of women in Scottish society in the nineteenth century and to compare historical evidence with representation of Scottish women in Scottish culture. Theoretical part summarizes differences between gender and social class, position of women in marriage and their social roles, and how women influenced Scottish literature in the nineteenth century. In the practical part of the thesis, presented data from theoretical part is compared with a novel written by a Scottish female author, Susan Ferrier. A book to be analyzed is her first novel, Marriage. She aims to deliver a moral message through her novel, and in context with this thesis, her viewpoint is important, as she incorporates her feminine viewpoint and her moral values into her story. Her female characters are then analyzed from a viewpoint of their behavior and cultural background and compared with data from theoretical part. The overall aim is to conclude, whether women were underestimated and how reality influenced their depiction in literature.
Skotské ženské hlasy
Keywords: ženy; Skotsko; devatenácté století; literatura; women; Scotland; nineteenth century; literature